A survey of growth and development issues of the Pacific islands - B. Bhaskara Rao; Kanhaiya Lal Sharma; Rup Singh; Nalini Lata (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper is a survey of some key variables with an international dimension and implications for growth and development policies in selected Pacific island countries. Results from a simple growth accounting exercise show that factor accumulation is the most dominant growth factor and that the contribution of total factor productivity is negligible. Therefore, increasing the investment rate to improve growth rate is a pragmatic medium-term policy option. Further, econometric analysis shows that foreign aid has a negligible effect on output and growth in Fiji, Solomon Islands and Papua New Guinea.
Keywords: O11; O40; O56; 330; macroeconomic analyses; economic growth; development issues; Pacific islands; Wirtschaftswachstum; Entwicklungspolitik; Insel; Pazifischer Raum